Hallux valgus deformity correction without fusion in children with cerebral palsy. Issue 2 (March 2017) - Bayhan, Ilhan A.; Kadhim, Muayad; Sees, Julieanne P.; Nishnianidze, Tristan; Rogers, Kenneth J.; Er, Mehmet S.; Miller, Freeman
Abstract : This study aimed to evaluate the outcomes of nonarthrodesis surgical treatment of hallux valgus (HV) deformity in children with cerebral palsy using radiographic and gait analysis parameters. There were 25 patients who had hallux valgus correction in 39 feet. The mean age at surgery was 15±2.8 years and the mean follow-up duration was 14.6 months. The first metatarsal osteotomy was performed in nine feet, bunionectomy in 25 feet, and Aiken osteotomy in 32 feet. None had metatarsophalangeal joint fusion. We observed a significant correlation between HV correction and other foot and ankle gait parameters. Our study showed correction of HV deformity at short-term follow-up without fusion of the metatarsophalangeal joint. Level of evidence: Level IV Therapeutic Studies.